Wildlife market and predisposition to zoonotic diseases in Ibadan, south-western Nigeria (2020)
Background: Recent cases of global epidemics rooted in zoonotic diseases’ transmission engendered the exploration of wildlife beliefs and practices toward disease transmission among vendors in wildlife markets. Objectives: The study explored the wildlife market practices in order to understand how the markets, attitudes and behaviours of traders can potentially influence the transmission of zoonotic diseases in Nigeria. Methods: The study employed a qualitative research method, involving non-participant observation and interviews of 22 consented vendors from five wildlife markers in Ibadan, Nigeria. Results: Wildlife vendors were neither grounded about animal-human transmission of diseases, nor hardly suspected their stock as a route or gateway for zoonoses’ transmission to humans. They also embraced metaphysical explanation of disease aetiology among them. Conclusion: Holistic and culturally-designed sensitisation about zoonoses targeting the wildlife vendors could facilitate the adoption of healthy practices when handling wildlife among them.